2016
DOI: 10.1136/bjophthalmol-2016-309162
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography of myopic choroidal neovascularisation

Abstract: We describe the OCT-A features of myopic CNV secondary to pathological myopia and demonstrate its high sensitivity and specificity for neovascular detection. Qualitative evaluation of OCT-A characteristics may allow one to recognise different patterns, possibly corresponding to different degrees of neovascular activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 13 publications
2
86
0
1
Order By: Relevance
“…In other words, instead of following the “1 subject = 1 hand” approach, we observed wrists as independent entities. This approach is relatively common in neurology as well as in other specialties . On the basis of such references and our everyday clinical experience with patients who have CTS, we decided to use data on all available wrists instead of omitting valuable information by choosing only 1 wrist per patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, instead of following the “1 subject = 1 hand” approach, we observed wrists as independent entities. This approach is relatively common in neurology as well as in other specialties . On the basis of such references and our everyday clinical experience with patients who have CTS, we decided to use data on all available wrists instead of omitting valuable information by choosing only 1 wrist per patient.…”
Section: Discussionmentioning
confidence: 99%
“…This approach is relatively common in neurology 8,12,[27][28][29][30][31][32]35,38 as well as in other specialties. [39][40][41] On the basis of such references and our everyday clinical experience with patients who have CTS, we decided to use data on all available wrists instead of omitting valuable information by choosing only 1 wrist per patient. Other limitations of this study included the fact that the US examiner was not blinded to electrodiagnostic findings and patient symptoms, since most of the patients were referred from an electrodiagnostic laboratory to a US laboratory for a clinical suspicion of CTS, and the same physician performing the US examination also gathered the clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…47 Previous studies have also indicated that in highly myopic eyes where general thinning of the retinal and choroidal layers are common, OCTA shows an overall reduced retinal capillary and choriocapillary density. 48,49 However, OCTA imaging in eyes with high myopia is challenging due to the steep curvature of the staphyloma causing poor focus or segmentation errors, areas of myopic degeneration can also lead to unmasking artefacts and difficulty imaging choroidal flow. 50 OCTA in retinal vascular diseases…”
Section: Progression Of Neovascularisation In Response To Treatmentmentioning
confidence: 99%
“…OCT angiography (OCTA) has been recently introduced, and it is able to examine the morphology of different types of CNVs in greater detail. Thus, Querques et al 15 examined 32 eyes with myopic CNVs by OCTA and reported that the CNVs might have different morphological features according to their activity. Miyata et al 16 reported that OCTA was able to confirm the presence of a CNV in 16 of the 17 eyes whose CNV was detected by FA.…”
Section: Introductionmentioning
confidence: 99%